Tweeting Stigma: An Exploration of Twitter Discourse Regarding Medications Used for Both Opioid Use Disorder and Chronic Pain - Dekeseredy, Patricia (Journal of drug issues, 2021)
We examined the content of tweets on the social media site Twitter to better understand the contemporary discourse about medications for opioid use disorder (MOUD), how this chat contributes to the pervasive underpinnings of drug addiction, chronic pain stigma, and the impact it has on demand and availability of treatment. A retrospective review of tweets over 3 months containing keywords buprenorphine, naltrexone, methadone, or bupe was conducted resulting in 5,068 tweets. A content analysis was carried out focusing on a subset of tweets. Themes emerged from including suspicion and conspiracy theories about MOUD, and frustration and lack of control over their treatment options. Other tweets shared stigmatizing language and attitudes related to OUD/MOUD (e.g., “Junkies”). Twitter is a rich source of data reflecting thoughts, opinions, and sentiments entities regarding MOUD. However, this information can contain malicious comments that perpetuate stigma for people with OUD and result in avoidance of treatment.